Biologic TNF inhibiting agents for treatment of inflammatory rheumatic diseases: Dosing patterns and related costs in Switzerland from a payers perspective - Jan Zeidler; Thomas Mittendorf; Rüdiger Müller; Johannes von Kempis (Health Economics Review, 2012)
Background: To obtain detailed real-life data on costs and dosing patterns in the utilisation of the TNF inhibitors adalimumab, etanercept, and infliximab in patients treated in Switzerland. Methods: Administrative claims processed by a major Swiss health insurer between 2005 and 2008 were analysed. Patients with inflammatory rheumatic diseases (IRDs) with at least one prescription for adalimumab, etanercept, or infliximab were identified. All-cause and disease-specific costs, as well as daily costs of treatment, were calculated. Dosing patterns and discontinuation rates were analysed. Results: A total of 555 IRD patients were identified. All-cause costs during the 12 months after the index event were 20,555CHF in the etanercept group, 24,152CHF in the adalimumab group, and 27,614CHF in the infliximab group. The most important cost driver was mean TNF inhibitor drug cost, which was 15,613CHF in the etanercept group, 19,166CHF in the adalimumab group, and 21,313CHF in the infliximab group. Discontinuation rates during the first year after the index event were 46.8% in etanercept, 41.3% in adalimumab, and 51.2% in the infliximab group. Rates of dosage increase were 13.3% in the etanercept group, 13.0% in the adalimumab group, and 14.1% in the infliximab group. When time on treatment was considered, daily costs of treatment were similar for etanercept and adalimumab, but were higher for infliximab. Conclusions: Marked differences in costs between subcutaneous and intravenous therapies were observed. Among the three groups of patients defined by TNF inhibitor treatment, costs for the infliximab group were highest during the year after the index event.
Keywords: 330; inflammatory rheumatic diseases; claims data; cost analysis; dosing patterns; Switzerland; Tumor necrosis factor inhibitor